(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The Internet has affected a revolution in our behavior and communication as well as in how we perceive and implement services. It offers new opportunities, like the self-service mode, a service operated mainly by the customer, which enables the more efficient and conscious use of resources, technologies, and knowledge, and thus an opportunity to imbue the service with sustainability. Yet, such a move does not occur in a vacuum, and it demands a corresponding behavioral shift by both provider and customer, who have the shared responsibility to educate themselves about, and to monitor, the sustainability of the service(s) in which they are interested. As such, it is the provider’s duty to supply a sustainable solution while the customer, who has obtained the information necessary to rate the alternatives, should choose the most sustainable one. The power of internet-based services is not only in their availability and ease of operation, but also in the efficiency manifested in the customer’s ability to perform several services together with virtually the same resources and effort. While these advantages can be easily superimposed on any design to ensure more sustainable services, the same properties may lead to increased, unsustainable consumerism.